Strategi Pembelajaran Matematika Pada Anak Usia Dini - Arie Widiyastuti; Rio Hermawan (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2022)
ABSTRACTEarly childhood mathematics learning strategies need to be packaged by considering various things so that mathematics does not give a heavy burden to children. Early childhood mathematics learning strategies that are quite effective are game learning as for the benefits, namely: it can help children learn mathematics based on correct mathematical concepts and avoid children being afraid of mathematics from the start can help children learn mathematics naturally through playing activities with various learning games mathematics. Learning strategies for mathematics that are appropriate for early childhood are: 1) Playing picture cards, numeracy skills, one-to-one correspondence skills, the ability to arrange the largest number of objects to the least and vice versa. 2) Making cakes, measuring abilities, numeracy skills, estimation skills, recognizing geometry. 3) Rhythmic motion patterns, the ability to identify patterns, the ability to imitate simple patterns, the ability to repeat simple patterns, the ability to make simple patterns in gardening, the ability to measure, the ability to count, the ability to compare. 4) Looking for stars the ability to classify colors, shapes, sizes, ability to compare high-low, the ability to sort numbers. Keywords: Early childhood education programs; Learning strategies; Math Learning Games. ABSTRAK Strategi pembelajaran matematika usia dini perlu dikemas dengan mempertimbangkan berbagai hal agar matematika tidak memberikan beban yang berat untuk anak. Strategi pembelajaran matematika anak usia dini yang cukup efektif adalah pembelajaran permainan adapun manfaatnya yaitu: dapat membantu anak belajar matematika berdasarkan konsep matematika yang benar dan menghindari anak ketakutan terhadap matematika sejak awal dapat membantu anak belajar matematika secara alami melalui kegiatan bermain dengan bermacam–macam permainan pembelajaran matematika. Strategi Pembelajaran matematika yang tepat untuk anak usia dini yaitu : 1) Bermain kartu gambar kemampuan berhitung, kemampuan korespondensi satu ke satu, kemampuan menyusun jumlah benda terbanyak hingga sedikit dan sebaliknya. 2) Membuat kue kemampuan mengukur, kemampuan berhitung, kemampuan estimasi, mengenal geometri. 3) Pola gerak berirama kemampuan mengindetifikasi pola, kemampuan meniru pola sederhana, kemampuan mengulang pola sederhana, kemampuan membuat pola sederhana berkebun kemampuan mengukur, kemampuan berhitung, kemampuan membandingkan. 4) Mencari bintang kemampuan klasifikasi warna, bentuk, ukuran, kemampuan membandingkan tinggi-rendah, kemampuan mengurutkan angka. KATA KUNCI: Pendidikan Anak Usia Dini; Strategi Pembelajaran; Permainan Pembelajaran Matematika.